PENGGUNAAN INSEKTISIDA PADA TANAMAN BAWANG MERAH LOKAL PALU DAN INTENSITAS SERANGAN HAMA Liriomyza, Sp DI GUNTARANO - Arfan; Lisa Indriani; Ratnawati; Kasman Jaya (FAKULTAS PERTANIAN UNIVERSITAS ALKHAIRAAT, 2022)
This study aims to determine the level of insecticide use and the intensity of pest leafminer fly attacks on local shallots in Palu in Guntarano Village. The research was conducted in Guntarano Village from April to July 2021. This study used a direct survey method using a structured questionnaire to obtain primary data by interviewing 10 respondent farmers. Respondents were selected based on their daily activities as local shallot farmers in Palu. Determination of respondents was carried out using a simple random sample method, while the observation of the percentage of Liriomyza sp pests was carried out at intervals of once every 7 days for 1 month. The results showed that the respondent farmers in cultivating shallots controlled herbivorous insects with the application of insecticides, with an interval of 1-3 times a week as many as 90% of respondent farmers had never participated in Integrated Pest Control (IPC) training activities. Farmers who used doses while the average percentage of Liriomyza, sp was the highest in the fourth week of 49.55%.